Reliability of Isotropic Model in Finite Element Simulation to Predict Wrinkling in Deep Drawing Process - Jasri, Mohamad; Wan Iryana, Wan Md Nor (EDP Sciences, 2016)
Deep drawing is one of important sheet metal processes used in manufacturing industry. Efforts have been conducted for many years to use advance computing software in understanding the metal forming process. Finite Element (FE) simulation is considered one of the best methods. The accuracy of FE application however depends on the type of hardening model being used as part of the material input.The aim of this studyis to investigate the reliability of isotropic hardening model in predicting wrinkling in deep drawing process. The finite element resultand the experimental result are compared visually for similarity as an indicator of the reliability of the hardening model